Benefits of Using Virtual Reality Glasses for Chemistry Lessons (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
This study aimed to evaluate virtual reality's impact on school students and analyze personal efficacy, self-esteem, and interest in an introductory chemistry course. We used a mixed-methods approach to improve our understanding of how these factors mediate pupils learning. The findings showed that the use of the virtual reality application positively impacted students’ personal efficacy, self-esteem, interest, and anxiety. The implications of these findings speak to the potential value of using virtual reality applications in higher education, especially in situations where distance learning is the only option and where the costs of real laboratories cannot be afforded